My field report, Spring 1986, Francis L. Moore - Moore, Francis L.et al (1986)
An annotated list of birds sighted by Francis Moore and five others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1986. Epson - sheet feed